Selective Requirements for Vascular Endothelial Cells and Circulating Factors in the Regulation of Retinal Neurogenesis - Dhakal, Susov; Rotem-Bamberger, Shahar; Sejd, Josilyn R.; Sebbagh, Meyrav; Ronin, Nathan; Frey, Ruth A.; Beitsch, Mya; Batty, Megan; Taler, Kineret; Blackerby, Jennifer F.; Inbal, Adi; Stenkamp, Deborah L. (Frontiers in Cell and Developmental Biology, 2021)
Development of the vertebrate eye requires signaling interactions between neural and non-neural tissues. Interactions between components of the vascular system and the developing neural retina have been difficult to decipher, however, due to the challenges of untangling these interactions from the roles of the vasculature in gas exchange. Here we use the embryonic zebrafish, which is not yet reliant upon hemoglobin-mediated oxygen transport, together with genetic strategies for 1) temporally-selective depletion of vascular endothelial cells, 2) elimination of blood flow through the circulation, and 3) elimination of cells of the erythroid lineage, including erythrocytes. The retinal phenotypes in these genetic systems were not identical, with endothelial cell-depleted retinas displaying laminar disorganization, cell death, reduced proliferation, and reduced cell differentiation. In contrast, the lack of blood flow resulted in a milder retinal phenotype showing reduced proliferation and reduced cell differentiation, indicating that an endothelial cell-derived factor(s) is/are required for laminar organization and cell survival. The lack of erythrocytes did not result in an obvious retinal phenotype, confirming that defects in retinal development that result from vascular manipulations are not due to poor gas exchange. These findings underscore the importance of the cardiovascular system supporting and controlling retinal development in ways other than supplying oxygen. In addition, these findings identify a key developmental window for these interactions and point to distinct functions for vascular endothelial cells vs. circulating factors.